Pengembangan Modul Fisika Berbasis Model Pembelajaran REACT Pada Materi Gelombang Bunyi Untuk Meningkatkan Kemampuan Memahami Konsep Siswa Kelas XI SMA - Januarti; Nur Islami; Yennita (Postgraduate, University of Mataram, 2023)
The goal of this study is to create a physics learning module for grade XI high school students based on the REACT learning model of sound wave content. The ADDIE model is being used in this research as part of a research and development project. The first step is to conduct a needs analysis and curriculum to see the problems in the field and then find a solution to overcome these problems, namely by developing a physics module based on the REACT learning model. The second step is designing, and the third is developing modules following the designed design. The produced physics modules have been approved by professionals and experts. The validation results show that the physics module based on the REACT learning model of sound wave material is declared valid. Before the product is applied to the field, the product is tested in small groups first on practitioners and students in small group trials. According to the answers from teachers and students, the physics module has a very good category, making it possible to use it in schools for the teaching process. The fourth phase entails putting the physics modules into practice or applying them to Class XI Science 1 students as an experimental class and Class XI Science 2 students as a control class that has already been evaluated for normalcy and homogeneity. It may be deduced that the data are normally distributed and that the control and experimental classes have homogeneous variance because the significant value for the control class was 0.200 and for the experimental class was 0.071. In the t-test, the average understanding ability of experimental class concepts was 76.30, and the standard deviation was 10.43, while the average understanding ability of control class concepts was 57.80, and the standard deviation was 11.44. Meanwhile, in the equality Means test, df and sig values were obtained. (2-tailed) or p-value, or H0 is rejected. The data thus confirm the proposed hypothesis, leading to the conclusion that the experimental class has a higher conceptual understanding than the control group.t=5.608, df=42, and sig. (2-tailed) or p-value = 0.000<0.005.